The effectiveness of e-mosque application management during Covid-19 Pandemic: An analysis of Masjid Abdullah Fahim - Fadzil, Mohd Ikhmal; Khamis, Kamarul Azman; Omar, Rusdi (IAEME Publication, 2020)
Islam is the official religion of Malaysia. Presently, the Muslim population in Malaysia is expected to grow over with an estimated 32.7 million Muslims in 2050. This will be nearly connected to the mosque's institution as an essential medium for the religious center of the Muslim community. The institution of the mosque is not only seen as a religious activity but also as a community center, administrative center, education center, center of economic activity and others. Currently, the Covid 19 pandermic has change the roles of the mosque's institution. The new normal adaptability towards development of the mosque institution is a crucial step need to be taken by the mosque’s management. The elements of social entrepreneurship clearly being shows when the mosque institutions are using some portion of their fund to assist the community who have been affected by the Covid 19 pandermic. The usability of the mosque E-application during covid-19 clearly contributed for the E-society linkages. Many efforts and writings have been gather to enhance the role of mosque institutions in Malaysia, mosque institutions as a hub for the Muslim community especially in the field of social and economic entrepreneurship have not been revived holistically especially in facing the new normal of Covid-19 pandermic.